a) \(\left(2x-5\right)^2-\left(x+2\right)^2=0\)
\(\Leftrightarrow\left(2x-5+x+2\right)\left(2x-5-x-2\right)=0\)
\(\Leftrightarrow\left(3x-3\right)\left(x-7\right)=0\)
b) Cách làm giống câu a
\(\left(3x^2+10x-8\right)^2=\left(5x^2-2x+10\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}3x^2+10x-8=5x^2-2x+10\\3x^2+10x-8=-5x^2+2x-10\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x^2-12x+18=0\\8x^2+8x+2=0\end{cases}}\)
\(TH1:2x^2-12x+18=0\)
\(\Leftrightarrow x^2-6x+9=0\)
\(\Leftrightarrow\left(x-3\right)^2=0\Leftrightarrow x=3\)
\(TH2:8x^2+8x+2=0\)
\(\Leftrightarrow4x^2+4x+1=0\)
\(\Leftrightarrow\left(2x+1\right)^2=0\)
\(\Leftrightarrow x=\frac{-1}{2}\)